Solidarumo principo vaidmuo ir reikšmė, aiškinant Lietuvos Respublikos Konstitucijoje įtvirtintą teisę į valstybės laiduojamą sveikatos apsaugą - Taminskaitė-Kočiūnė, Gabrielė (Vilnius University Open Series, 2024)
This article analyses the commitments of Lithuania in the field of health care and the instruments used by the State to implement these commitments. It also analyses the case law of the Constitutional Court of the Republic of Lithuania and the Court of Justice of the European Union, which is necessary to reveal the implications of the chosen measures for the rights and obligations of society and individuals. This right to health protection, as a constitutional right, and the peculiarities of its enforcement are the main subject of the analysis of this article.